Evaluasi Aplikasi Parkir Sepeda Motor menggunakan User Experience Quetionare (UEQ) - Rahmawati, Eka; Agustina, Candra (Informatics and Computer Engineering Journal, 2021)
Motorcycle parking application is an information system that is used to make it easier to record entry and exit parking, parking duration, and find out how much space is available for parking. One of the tools used to evaluate is the User Experience Quetinonare or UEQ. UEQ can measure six user perspectives, namely attractiveness, sharpness, efficiency, dependability, stimulation, novelty. The questionnaire was distributed to 20 respondents who had used the application. The data is then processed using Data Analisys Tools that has been provided by UEQ. The results of data processing show that the Attractiveness aspect has a value of 1.24, Perspicuity has a value of 1.54, Efficiency has a value of 1.33, Dependability has a value of 1.19, Stimulation has a value of 1.58 and Novelty has a value of 0.92. The six aspects have a value > 0.8 so that the parking application has a positive evaluation.